The Qualitative Study: Family Experiences in Facing Catastrophic Disease Emergencies in the Emergency Department: Qualitative Study: Family Experiences in Facing Catastrophic Disease Emergencies in the Emergency Department - Sari, Sofiani (JURNAL KESMAS DAN GIZI (JKG), 2023)
Catastrophic illness emergencies are often emotional and challenging experiences for patients' families. This study aims to explore families' experiences in dealing with catastrophic illness emergencies in the Emergency Department (ED). This research used a qualitative study with a phenomenological approach. Data were collected through in-depth interviews with family members of patients experiencing catastrophic illnesses and treated in the ED. The findings indicate that families face various emotional, psychological, and social challenges, along with coping strategies to deal with these situations. The study concludes by highlighting the importance of psychosocial support for patients' families in dealing with catastrophic illness emergencies.